Slash and burn and fires in Indonesia: a comment - Tacconi, L.; Vayda, A.P. (2006)
A paper published in Ecological Economics [Varma, A. 2003. The economics of slash and burn: a case study of the 1997–1998 Indonesian forest fires. Ecological Economics 46,159–171] claims to show that slash and burn agriculture is socially inefficient and should be banned. However, its conclusions and recommendations are flawed. It defines slash and burn agriculture too broadly and misrepresents the nature and causes of the 1997–98 fires by virtue of attributing them entirely to slash and burn agriculture. Its economic assessment of the costs of the fires is also problematic. The recommendations to ban land-clearing fires and to provide alternative livelihoods to slash and burn farmers cannot be supported.